Peningkatan Engagement dalam Promosi Digital melalui Pembuatan Video Produk Pakan Ternak pada Salah Satu Perusahaan di Sidoarjo - Putri Zulfa; Heru Utomo; Fatkhur Rochman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to develop a promotional video for laying hen feed products using Wondershare Filmora and to evaluate its effectiveness in increasing audience engagement. The research employed the Action Research method, which consisted of four stages: (planning, action, observation, and reflection). Data were collected through observations, interviews, documentation, and questionnaires distributed to 29 respondents. The collected data were analyzed using the EPIC Model to evaluate the effectiveness of the promotional video and the Engagement Rate metric to measure audience interaction on YouTube. The results indicated that the promotional video delivered product information in a more comprehensive and engaging manner. The EPIC Rate increased from 4.3 in the first cycle to 4.375 in the second cycle, placing both results in the very effective category. Furthermore, the Engagement Rate increased from 1.82% to 13.67%, indicating a very high level of audience engagement. The findings indicate that the developed promotional video is an effective digital marketing medium for communicating product information and enhancing audience engagement on YouTube. Therefore, the company is encouraged to provide comprehensive product information and consistently publish promotional videos to strengthen its digital marketing performance.